2017
DOI: 10.2147/jpr.s129540
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Norwegian Pain Sensitivity Questionnaire

Abstract: Background and purposeThere is a large variation in people’s reactions to painful stimuli. Although some conditions are more painful, the variation between people is larger than the reaction to pain across conditions. Induced experimental pain is one way to assess some aspects of these differences in pain perception. Experimental nociceptive testing is time consuming and not always feasible in a clinical setting. In order to overcome the obstacles of assessing pain sensitivity using experimental stimulation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 24 publications
5
30
1
Order By: Relevance
“…8 Exploratory factor analysis (EFA) was conducted with the principal component factor method, under the assumption of null uniquenesses, for guidance on factor retention and eigenvalue comparability with previous works. 23,38,48 Item uniquenesses were of similar size and within acceptable margins among the models explored (<.60 for 1-factor solution, <.40 for 2 or more factor solutions), with only minor exceptions. 36 Both orthogonal and oblique rotations were explored to reflect different perspectives on the data.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…8 Exploratory factor analysis (EFA) was conducted with the principal component factor method, under the assumption of null uniquenesses, for guidance on factor retention and eigenvalue comparability with previous works. 23,38,48 Item uniquenesses were of similar size and within acceptable margins among the models explored (<.60 for 1-factor solution, <.40 for 2 or more factor solutions), with only minor exceptions. 36 Both orthogonal and oblique rotations were explored to reflect different perspectives on the data.…”
Section: Discussionmentioning
confidence: 75%
“…The identified PSQ structures overcome limitations of previous studies, which did not formally explore the incidental higher-order structure of the PSQ under the proposed 3-score system and did not assess structural consistency between genders. 23,32,38,48 Participants equally represented both genders, spanning the entire adult age range. Results were robust to the exclusion of participants with the presence of any chronic pain or reporting extreme values on the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A validation in chronic pain patients [16], and a separate English language validation of the PSQ [17] have been published. However, the cohort sizes from which stimulus response correlations with PSQ scores are published are limited (406 subjects in [16], 319 subjects in [18], 136 subjects in [17], 103 [19], 182 [20] and 331 [21]). More recently, Grundström et al (2019) demonstrated an association between PSQ total score and both temperature and pressure thresholds, not including the CPT, in a sample of 37 women with persistent pelvic pain and 55 control women, though associations were notably stronger in the chronic pain subgroup [22].…”
Section: Introductionmentioning
confidence: 99%